Strategi Hubungan Masyarakat Pascasarjana Sekolah Tinggi Ilmu Administrasi Mandala Indonesia (STIAMI) Dalam Membentuk Citra Positif - Susilowati; Dhefine Armelsa; Duneti - (LPPM Universitas Bina Sarana Informatika, 2022)
A university cannot be separated from various cases, especially in the Postgraduate program, it is very important to always maintain an image because it is related to public trust in the quality possessed by an educational institution. Public Relations of the Postgraduate School of Administrative Sciences at Mandala Indonesia which requires making a strategy to improve a positive image. The concept used in analyzing the Public Relations strategy stated by Cutlip. The purpose of the study was to determine the Public Relations strategy of the Postgraduate School of Administrative Sciences at Mandala Indonesia in improving the image with the Media Relations program. In this study using a qualitative approach and descriptive methods. Data collection techniques used in this study were interviews, non-participant observations by taking primary and secondary data. The results of this study are the Postgraduate Public Relations Strategy of the Mandala Indonesian College of Administrative Sciences in increasing a positive image in media relations program activities in each of its activities can build a positive image in accordance with the objectives of the public relations strategy by carrying out four stages of communication strategies, namely defining the problem, planning and programming, taking action and communicating, Program evaluation.